2013
DOI: 10.1111/jace.12597
|View full text |Cite
|
Sign up to set email alerts
|

3D Simulation of Borosilicate Glass All‐Electric Melting Furnaces

Abstract: Two all‐electric melting furnaces, 15t/d and 36t/d, were simulated and analyzed with the ANSYS FLUENT 14.0 software add‐on MHD module. The electric power density distribution, temperature distribution, and velocity field in the glass furnaces of these two models were analyzed. Electric power density and temperature are found to increase initially and then decrease from the center of the furnace to the side wall in a horizontal direction. Similar trend is observed from top to bottom in a vertical direction. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…Al(OH) 3 of the second parabola. Fluctuations on HWI-Al-19 and HWI-Al-28 foaming curves were caused by bursting of large bubbles.…”
Section: Mass (G) Mass (G) Mass (G) Mass (G) Mass (G)mentioning
confidence: 99%
See 1 more Smart Citation
“…Al(OH) 3 of the second parabola. Fluctuations on HWI-Al-19 and HWI-Al-28 foaming curves were caused by bursting of large bubbles.…”
Section: Mass (G) Mass (G) Mass (G) Mass (G) Mass (G)mentioning
confidence: 99%
“…Unlike in fuel-heated furnaces, where the batch is heated from both sides, melting proceeds predominantly from the cold-cap bottom in an electric glass-melting furnace. [1][2][3][4] Thus, the glass batch is converted to molten glass as it moves down through the cold cap from the top surface to the hot interface with the melt pool. As Figure 1 illustrates, the cold cap consists of several zones, from the dehydrating zone through the core layer to the conversion zone.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this is not the case of the cold cap region of melters. Mathematical models have successfully simulated fluid flow and heat transfer in the melt pool and furnace atmosphere to address energy economy, glass product quality, and environmental pollution issues, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] but the heat transfer from the melt pool to the cold cap has not been the main focus. Even though certain aspects of glass processing have been studied in minute detail, [23][24][25] the complexity of chemical and physical phenomena occurring in the batch blanket and at the batch-melt and batch-gas interfaces present formidable obstacles to executing realistic models.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Since the invention of molybdenum electrodes in 1950s, the electric melting plays an important role in industrial glass furnace, for example the all-electric furnace and electric boosting furnace. 13) Most of all-electric glass furnaces have been used for special glasses and the particular glasses with significant volatile constituents, as the furnaces usually present small size and simple structure. 4,5) In the electric boosting furnace, the electric boosting system is incorporated into fuel-fired glass furnace to improve the glass melting quality and glass production.…”
Section: Introductionmentioning
confidence: 99%
“…Li 13) analyzes two all-electric melting furnaces with different production of 15 t/d and 36 t/d. It is found that the electric power density and temperature increase initially, then they decrease from center of glass furnace to the sidewall in horizontal direction, or decrease from top of glass furnace to bottom in vertical direction.…”
Section: Introductionmentioning
confidence: 99%